"A Bowl of Vegetables With Someone You Love": Faith, Health and Workplace Well-Being. Issue 7 (September 2021) - Terry, Paul E.
Worksite health and well-being initiatives will ideally be integrated with employers' efforts to address diversity, equity and inclusion issues. Social Determinants of Health (SDOH) include race, class, community health, income and other variables that companies can play a role in ameliorating. As much as spirituality is commonly espoused as a component of a holistic approach to health promotion, making space to discuss faith and health remains an uncommon strategy in the workplace wellness movement. Recognizing the value on investment (VOI) in wellness has eclipsed a return on investment as a driver of an employer's well-being strategy. This editorial argues that making space for learning about faith and health will intersect in vital ways with anti-racism work, diversity programs and similar efforts to eliminate health inequities, address SDOH and bolster the VOI of worksite well-being initiatives. A fictional dialogue between executives is used to review these issues and related literature.